PIMS-TS- (Paediatric Inflammatory Multisystem Syndrome - Temporally Associated with SARS-CoV-2)- a new challenging medical condition - Robert Dubel; Kinga Ruszel; Wiktoria Chodun; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2021)
At the beginning of pandemic of SARS-CoV-2 children were thought to go through COVID 19 in  a definitely milder way than adults, in most cases even asymptomatically. However, even though the period of infection in pediatric patients is benign, SARS-CoV-2 found a way to take its toll on children's health. Here comes PIMS-TS:  Paediatric inflammatory multisystem syndrome - temporally associated with SARS-CoV-2 (PIMS-TS) [ICD-10: U 10.9]. Since the global pandemic of COVID-19 is still on the go, for over a year now, SARS-CoV-2 tends to constantly mutate and affect children at increasingly young age either by oligosymptomatic respiratory viral infection, or more distant SARS-CoV-2-related medical condition- PIMS-TS.    Paediatric inflammatory multisystem syndrome - temporally associated with SARS-CoV-2 (PIMS-TS), or Multisystem inflammatory syndrome in children (MIS-C) as it's also called, is a rare systemic disease manifested by persistent fever and extreme inflammatory reaction following exposure to SARS-CoV-2, 2-4 weeks before the symptoms occur. It's a brand new medical condition, described for the first time in May 2020. PIMS-TS affects 1 out of 1000 children infected with SARS-CoV-2 and can lead to very dangerous cardiological complications such as acute pancarditis, shock or aneurysms of coronary arteries. Efficient treatment performed in the accurate time and hospitalization in ICU allow to overcome PIMS-TS in the prevalent number of patients and get better in a few days. Mortality of PIMS-TS ranges from 1,5% to 2% of all cases.